Introducing the hydrate gel membrane technology for filtration of mine tailings. (May 2019) - Liu, Di; Edraki, Mansour; Malekizadeh, Ali; Schenk, Peer M.; Berry, Luke
Highlights: Hydrate gel membrane is a novel and inexpensive means for filtering mine tailings. The gel membrane can significantly improve the filtrate water quality. Cake moisture and thickness was comparable with other filter aids. The technology showed great potential for filtering thickener underflow. Abstract: Aluminium hydroxide hydrate membrane technology was recently developed as a novel, simple, and low cost gel-based filtration system. Previous work examined the properties of the gel and showed that it has great potential to be used as separation means for filtration of suspended solids. In this study, the gel was applied to the dewatering of copper mine tailings for the first time. The filtration process efficiency was measured by filtration rate, the turbidity of the supernatant liquid, cake thickness and the final cake moisture content. The filtration performance was also tested against other filter aids typically used in mining operations. It is evident that the application of hydrate gel membrane for filtrating copper tailings is encouraging. It was found that the comparative advantage of the hydrate membrane lies in producing much lower turbidity water than other filter aids. Although the flux rate of the hydrate gel membrane was a little lower than the three filter aids tested, the cake moisture and thickness was comparable. Also, the hydrate gel membrane could be easily spread out against a retaining fabric and worked well at low to no pressure, with optimum flux rates at about 10 psi and acceptable flux rate at zero pressure. This study suggests that hydrate gel membranes can be applied in the mining industry, especially where operating and capital costs are a concern and operators are seeking low turbidity water and/or a cake suitable for stacking or reprocessing. The technology showed great potential to be utilized for filtering thickener underflow tailings.